Identifying challenges in drinking water supplies: assessment of boil water advisories in Norway (2008–2019) - Susanne Hyllestad (IWA Publishing, 2021)
The issuing of boil water advisories (BWAs) is a widely used response to microbiological contamination events in drinking water supply systems, and may therefore serve as an indicator for the access to safe drinking water. To supplement data source on the overall status of water supply systems (WSSs) in Norway, we analysed public media reports published in Norway to assess trends, causes, geographical and seasonal distribution of BWAs issued during the period 2008–2019. We identified 1,108 BWA events increasingly reported over the study period but characterised by a decreasing trend in time with respect to duration. The two main frequent causes for BWA were detection of faecal indicator bacteria (42.6%) and risk of contaminants intrusion in the distribution system (21%). We observed higher reporting rates in summer and autumn compared with winter, and higher reporting rates in Northern and Eastern Norwegian regions compared with the Central region. The results of this study could serve as supplementary information to better understand the overall status among WSSs in Norway, particularly in case of recurrent BWA's events, as well as suggest the relevance of BWAs' monitoring in identifying risk factors and planning targeted interventions. HIGHLIGHTS Trends of boil water advisories.; Assessment of risks in drinking water supplies.; Media reports as data source for drinking water status.;